CONTROL OVER THE USE OF STATE FUNDS - POPOVYCH, Serhii (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article is devoted to the study of control over the use of public funds on the basis of local budgets of Ukraine, considers the essence, principles, functions, current tasks, types, forms and methods of public financial control. The influence of state control of local budgets is revealed, the principles of public administration in the part of finances are substantiated.The purpose is to reveal the influence of state control of local budgets, the principles of public administration in the field of finance are substantiated.The control of public finances is carried out in order to ensure legality in the field of relations with special state bodies, prevention of financial violations, strengthening financial discipline in the formation, distribution and use of public funds. The role of public financial control is constantly growing, as it is an important means of administrative and legal regulation of economic, political and social processes in Ukraine, is not only a guarantee of transparency of state bodies and local governments, but also a guarantee of financial stability. Control over public funds is especially important in the field of public administration, as the effectiveness of its implementation depends on the successful development of the state economy. In addition, control over the distribution and use of public funds to the standards of public financial control will improve the coordination of regulatory bodies in managing budget processes at all levels of the budget, the implementation of control measures and management decisions.The practical application of state control, in particular the conduct of effective audits, will increase the effectiveness of control measures, create conditions for coordination of control bodies and controlled entities of state financial control, increase revenues to local budgets. The differences of the world's leading countries in terms of public financial control are presented.
Keywords: budget; financial control; financial violations; audit; local budget; receivables; expenditures; State Audit